Anatomy of a metropolis. The changing distribution of people and jobs within the New York metropolitan region. With the assistance of M. Abelson, A.K. Campbell, L. Lerner, a.o. [Foreword by E.S. Mason] (Doubleday, 1962)
With graphs, map, reg. and tabs.